Clinical efficacy and safety between continuous rotary and reciprocating root canal instrumentation systems - Chaudhary, Govind Kumar; Alam, Md. Shamsul; Hossain, Mozammal (Journal of Chitwan Medical College, 2021)
Background: The single file reciprocating system prepares the canal quickly with a better centric ability and has increased resistance to cyclic fatigue compared to the continuous rotary file system. However, the former file system was associated with more postoperative pain than the latter. The goal of the present study was to evaluate and compare the clinical efficacy and safety between continuous rotary and reciprocating instrumentation systems.Methods: Fifty patients who fulfilled specific inclusion criteria were assigned into 2 groups according to the root canal instrumentation technique used, ProTaper Gold and WaveOne Gold. Endodontic treatment was performed in a single visit. Patients were instructed to rate the intensity of postoperative pain on Visual Analog Scale and to record the quantity of prescribed analgesic medication taken after 24 hours, 48 hours, 72 hours, and 7 days. Time of root canal preparation, duration of pain, and incidence of procedural errors such as ledging, transportation, root perforation, and instrument separation were recorded. The data was collected from October 2018 to September 2019. SPSS version 24 was used for data analysis.Results: This study revealed no statistically significant difference between instrumentation groups with relevance to postoperative pain and analgesic medication intake (P > 0.05). Canal preparation time was significantly shorter in reciprocating group compared to rotary group (P < 0.001). Further, the incidence of procedural errors in both instrumentation group was found statistically insignificant (P > 0.05).Conclusions: Continuous rotary and reciprocating systems were both found to have similar clinical efficacy and safety and hence can be used to instrument the root canals.